(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
“Giant” is the most frequent word in commemorating Avedis Donabedian. Rarely there was such agreement among scholars worldwide to define the role of a scientist in the field of Public Health. And it’s impossible to disagree. Avedis Donabedian had a really huge role in the progress in Public Health studies. It’s not exaggerated even to say that his insights influenced all scientific research.